Suporte ao uso de álcool e drogas na atenção primária: um estudo com equipes de Natal/RN - Lima, Ana Izabel Oliveira (2014)
National surveys indicate that 6.8 % of the brazilian population is dependent on alcohol and 1 % dependent on illicit drugs, representing a significant portion of the population affected by this issue . Primary Care becomes instrumental in expanding the coverage of this demand and in reducing unnecessary referrals for specialized care. This study aimed to investigate the responsiveness and institutional support of Primary Care Teams in relation to the demands of alcohol and drugs users. The research was conducted in a Family Health Unit in West Sanitary District of Natal City. With quantitative and qualitative nature, our study consisted of two stages. At first, we performed a mapping of alcohol and other drugs abusive use in a sample of the population assisted by Family Heath Teams, using sociodemographic questionnaire and ASSIST (Alcohol, Smoking and Substance Involvement Screening Test). 406 questionnaires were completed. Of these questionnaires, 27.8% are men and 72.2% women, of which 56% are between 20 and 39 years-old, they are housewives, have a stable relationship and are consumers of tobacco (37.6%), marijuana (13%) and especially alcohol (57%). In second stage, two Conversation Circles with Family Health Teams and the referential Family Health Support Center were formed to discuss the data of the mapping realized in the previous phase. The circles, which had participation of 20 of the 37 professional teams from Family Health and 2 from Family Health Support Center, showed a lack of professional training in the subject; inability of the healthcare network in the user embracement; belief of professionals that nothing can be done when matter is alcohol and drugs; and referencing as the only care action performed by teams. Thus we point out the need to support an approach on issues of alcohol and drugs which consider gender issues, investing in Harm Reduction Policy as a possibility of working in this context for recognizing each user in their uniqueness and strategizing with them to promote health in a broad and contextualized way